Negotiation Style Comparisons by Gender among Greater China - Tu, Yu-Te (Journal of Social and Development Sciences, 2012)
As the economics within Greater China become more internally linked together, it becomes increasingly important to understand the nuances of each culture encompassed by this term. There is very little comparing the negotiation styles of Chinese who live in Taiwan, Hong Kong, and Mainland China among themselves. To fill the gap, the present research focuses on negotiations style comparison by gender among Chinese in Taiwan, Hong Kong, and Mainland China. The population was chosen from public companies listed under the stock markets. Data was collected using an online survey technique. SPSS was used to conduct data analyses, and a variety of statistical measures were used, including descriptive statistics and MANOVA, and coefficient alphas was reported for modified instruments in order to address reliability and validity of the instrument. The study found that only the factual negotiation style showed a significant relationship with gender among the three regions. The researcher suggests that the negotiators still need to be trained in body language, strategies, temper control, international manners, and customs. A better knowledge of negotiation should be helpful in understanding business and in realizing which negotiation styles are most appropriate for a particular country. The appropriate negotiation skills can bring more competitive advantages and benefits.